2022
DOI: 10.3390/jcm12010221
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Adds Valuable Information Regarding the Presence of DKA in Children with New-Onset T1DM

Abstract: Diabetic ketoacidosis (DKA) is an acute life-threatening complication occurring mainly at the onset of type 1 diabetes mellitus. The neutrophil-to-lymphocyte ratio (NLR), a marker for systemic inflammation, has recently generated increasing interest in many chronic diseases. The aim of this cross-sectional study was to determine the value of the neutrophil-to-lymphocyte ratio (NLR) in association with DKA severity across these cases. A total of 155 children with new-onset type 1 DM from one large center were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(50 reference statements)
2
5
0
Order By: Relevance
“…In moderate cases of DKA value, it was 3.71; 1.98-4.85. In severe cases, NLR median value was 5.77; 4.04-9.63 [95]. NLR may be a possible predictor of systemic inflammation severity in DKA [98].…”
Section: Neutrophil-to-lymphocyte Ratio (Nlr) In Dka Patientsmentioning
confidence: 90%
See 1 more Smart Citation
“…In moderate cases of DKA value, it was 3.71; 1.98-4.85. In severe cases, NLR median value was 5.77; 4.04-9.63 [95]. NLR may be a possible predictor of systemic inflammation severity in DKA [98].…”
Section: Neutrophil-to-lymphocyte Ratio (Nlr) In Dka Patientsmentioning
confidence: 90%
“…NLR shows adaptive and innate immune response functions [91][92][93][94]. Several studies have found an increased NLR in patients with DKA [82,[95][96][97]. In a study, the median NLR in patients without ketoacidosis was 1.11; 0.80-1.80.…”
Section: Neutrophil-to-lymphocyte Ratio (Nlr) In Dka Patientsmentioning
confidence: 99%
“…Gender Dichotomous Dichotomous (Male/Female) [14,19] Paternal level of education Ordinal (ISCED 0-7) Dichotomous (ISCED > 4 vs. ISCED ≤ 4) Higher education vs. no higher education [13,14,[21][22][23][24][25][26][27] Maternal level of education [13,14,43] Neutrophil to lymphocyte ratio Continuous Continuous [44][45][46] Mean platelet volume Continuous Continuous [47][48][49] Specifically, we adjusted disease duration and the BMI Z-score by centering them around the sample's mean for use in binary logistic regression. This process involved subtracting the sample mean from each data point within these variables, a step undertaken to diminish the numerical instability that can arise in regression models due to large variable values.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…A growing body of research focuses on CBC-derived indices in chronic diseases, including diabetes. Among these, the most evaluated index in diabetic patients has been the neutrophil-to-lymphocyte ratio (NLR) [22][23][24][25]. However, while much of the research has centered on the role of neutrophils and lymphocytes, monocytes also appear to exert a notable impact on the pathogenesis of T1DM [26][27][28][29] and its complications, such as cerebral edema and AKI [30,31].…”
Section: Introductionmentioning
confidence: 99%